Randomised controlled trial of a psychosocial digital health application to promote coping for caregivers of patients undergoing haematopoietic stem cell transplantation: a study protocol for the BMT-CARE app - Areej El-Jawahri; Jamie M Jacobs; Jennifer S Temel; Joseph A Greer; Dustin J Rabideau; Nora K Horick; Allison J Applebaum; Kelcie D Willis; Anna Barata; Madison Freese; Ashley Nelson; Lara N Traeger (BMJ Open)
Introduction Caregivers of patients undergoing haematopoietic stem cell transplantation (HSCT) experience tremendous psychological distress before, during and after HSCT. However, few interventions are tailored to the protracted needs of these caregivers while considering scalability and accessibility. We previously developed an evidence-based intervention for caregivers of patients undergoing HSCT that improved quality of life (QOL), caregiving burden and mood. We have since adapted this clinician-delivered intervention into a self-administered, digital health application (BMT-CARE app) and are currently evaluating the effect of this intervention on QOL in caregivers of patients receiving HSCT.Methods and analysis The study design is a non-blinded randomised controlled trial of a digital health intervention for caregivers of patients undergoing HSCT at the Massachusetts General Hospital Cancer Center. We are enrolling and randomising 125 caregivers to receive the BMT-CARE app or usual care in a 1:1 assignment, stratifying by transplant type (autologous vs allogeneic). Caregivers assigned to the BMT-CARE app complete five self-guided modules designed to improve coping and stress management prior to and up to 60 days post-HSCT. The modules include interactive, gamified features and video vignettes to optimise engagement. Participants complete questionnaires at baseline and days 10, 60 and 100 post-HSCT. The primary outcome is comparison of QOL at day 60 post-HSCT. Secondary outcomes include caregiver burden, anxiety and depression symptoms, as well as post-traumatic stress symptoms. We are also exploring the usability of the BMT-CARE app to inform refinements prior to future testing.Ethics and dissemination The study is funded by the Leukemia and Lymphoma Society and approved by the Dana-Farber/Harvard Cancer Center Institutional Review Board (Protocol #22–634 v.1.5). The results of this study will be reported in accordance with the Consolidated Standards of Reporting Trials statement for non-pharmacological trials. Results will be disseminated at scientific meetings and in peer-reviewed journals.Trial registration number NCT05709912; Pre-results.